PENGARUH PERSEPSI KEADILAN ORGANISASI, PERSEPSI DUKUNGAN ORGANISASI, COLLECTIVE SELF-ESTEEM, DAN ALIENASI KERJA TERHADAP PERILAKU IDEAL KEWARGAAN ORGANISASI - , Budi Santosa, Prof. Th. Dicky Hastjarjo. Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aimed to examine the relationship between organizational citizenship behavior (OCB) and four other variables that are assumed to be the antecedents. The four variables was perceived organizational justice (POJ), perceived organizational support (POS), collective self-esteem (CSE), and work alienation (WA). The first hypothesis was on the relationship between the five variables. The second hypothesis concerned the mediating role of POS in the relationship between POJ and CSE, mediating role of CSE in the relationship between POS and WA, and mediating role of WA in the relationship between CSE and OCB. This study also aimed to examine the relationship between OCB and the four antecedent variables, based on the proposed model. Variables in this study were measured by scales adapted from scales that had been developed and used in previous studies. Analysis of the relationship amongs variables conducted by bivariate correlation analysis of Pearsonâs product-moment. Technique recommended by Baron and Kenny (1986) was used to analyze the mediation. To examine the proposed model, path-analysis was performed by multiple regression techniques. Results showed that the variables had correlation on sig. 0.01, and WA had negative correlation with the other variables. Results of mediation analysis showed that POS mediated the relationship between OCB and CSE, CSE mediated the relationship between POS and WA, and WA mediated the relationship between CSE and OCB. The path-analysis of the proposed model yielded reduction models that could explain the influence of the four variables on OCB.